Distinct profiles of immunoglobulin G-binding-protein expression by invasive serotype M1 isolates of Streptococcus pyogenes. - Raeder, R (1995)
Analysis of immunoglobulin G (IgG)-binding-protein expression by invasive group A streptococcal isolates of the M1 serotype collected as part of a Centers for Disease Control and Prevention surveillance study revealed two distinct phenotypes. One group of type M1 isolates expressed a surface protein reactive with all four human IgG subclasses (type IIo), while a second group expressed a surface protein demonstrating significant reactivity only with human IgG3 (type IIb). The functional forms of IgG-binding protein were antigenically related, and both were recognized by a rabbit polyclonal antiserum to serotype M1 but not by normal rabbit serum. While the quantities of antigenic M1 protein present in the extracts of representative isolates displaying each phenotype differed, the functional differences were found to be qualitative and not solely quantitative. The IgG-binding properties of these antigenically related M1 proteins could be readily distinguished from those of another IgG-binding protein, protein H. Type M1 isolates of the IIb phenotype differed from those of the IIo phenotype by secreting larger amounts of a casein-hydrolyzing protease into culture supernatants.